Meigs’ Syndrome Associated with Giant Granulosa Cell Tumor of the Ovary - Erkanlı, Serkan; Kuşçu, Esra; Bağış, Tayfun; Tarım, Ebru; Kılıçdağ, Esra; Haberal, Ali (Gynecology Obstetrics & Reproductive Medicine, 2006)
Presentation of rare occurrence of Meigs’ syndrome associated with giant granulosa- cell tumor of the ov ary. Giant granulosa-cell tumor of the ov ary, in a patient presenting with ascites, and bilateral pleural effusion, which rapidly dried up on excision. Meigs’ syndrome should alway s be kept in mind, not to mistakenly up-stage a patient, presenting with ascites and pleural fluid along with an ovarian mass